2021
DOI: 10.1177/11206721211004391
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal dexamethasone insert in diabetic macular edema super-refractory to anti-vascular endothelial growth factor therapy

Abstract: Background: Some patients with diabetic macular edema (DME) fail to completely respond to anti-vascular endothelial growth factor (VEGF) therapy. These patients have a high treatment burden in the absence of significant improvement. We investigate the role of intravitreal dexamethasone insert (IDI) in eyes with super-refractory DME. Methods: A non-randomized interventional study was performed among eyes with super-refractory DME refractory to anti-VEGF therapy. Eyes were treated with IDI after failing clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A recent Diabetic Retinopathy Clinical Research (DRCR) study reported no significant differences in 2-year visual outcome for DME between aflibercept monotherapy and bevacizumab replaced with aflibercept, suggesting a rescue effect of later applied IVA [ 25 ]. However, in cases that do not respond to IVA, alternative methods such as steroids, laser treatment, or even surgery may be needed to treat the DME [ 15 , 26 ]. Of the four refractory cases presented in our study, two were treated with focal laser photocoagulation, while the others received intravitreal corticosteroid injections.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Diabetic Retinopathy Clinical Research (DRCR) study reported no significant differences in 2-year visual outcome for DME between aflibercept monotherapy and bevacizumab replaced with aflibercept, suggesting a rescue effect of later applied IVA [ 25 ]. However, in cases that do not respond to IVA, alternative methods such as steroids, laser treatment, or even surgery may be needed to treat the DME [ 15 , 26 ]. Of the four refractory cases presented in our study, two were treated with focal laser photocoagulation, while the others received intravitreal corticosteroid injections.…”
Section: Discussionmentioning
confidence: 99%
“…A recent non-randomized interventional study investigated the possible role of a DEX implant in a limited sample of eyes with DME refractory to serial intravitreal injections [ 61 ]. Six eyes that had not responded clinically to previous aflibercept injections had DEX implants.…”
Section: Switching From Anti-vegf Therapy To Dex Implant In Dmementioning
confidence: 99%
“…The mean BCVA improved and the CST decreased after one year. The authors concluded that the DEX implant showed good anatomic improvement and moderate visual improvement in eyes with DME that were resistant to repeated intravitreal injections [ 61 ].…”
Section: Switching From Anti-vegf Therapy To Dex Implant In Dmementioning
confidence: 99%
“…Considering DME refractory to a large number of intravitreal injections, a recent non-randomized interventional study explored the potential role of DEX implant in a small sample of such eyes. 54 Six eyes with failed clinical response after a mean of 43.5 (range 15–58) prior anti-VEGF injections, and all with failed aflibercept, underwent DEX implant plus a breakthrough anti-VEGF injection when required. At 1 year, the mean BCVA improved from 0.475 to 0.375 logMAR and central subfield thickness (CST) reduced from 386.5 to 315 μm.…”
Section: Dex Intravitreal Implant and Anti-vegf Injections For Dmementioning
confidence: 99%